2015
DOI: 10.1532/hsf.1367
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Methylprednisolone Improves Myocardial Protection during On-Pump Coronary Artery Bypass Surgery

Abstract: This study demonstrates that methylprednisolone is effective for ensuring better myocardial protection during cardiac surgery by suppressing the inflammatory response via decreasing the levels of IL-6 and by increasing anti-inflammatory activity through IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A previous systematic review and meta-analysis published in 2011 found that corticosteroids were not associated with any significant reduction in clinically important adverse outcomes from heart surgery [19]. Since that review was published, 8 randomized controlled trials (RCTs) including 2 trials [20,21] with large population sample sizes have been published [20][21][22][23][24][25][26][27]. Thus, an updated systematic review and meta-analysis is warranted to summarize the current understanding of the use of corticosteroids in patients undergoing heart surgery with CPB.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review and meta-analysis published in 2011 found that corticosteroids were not associated with any significant reduction in clinically important adverse outcomes from heart surgery [19]. Since that review was published, 8 randomized controlled trials (RCTs) including 2 trials [20,21] with large population sample sizes have been published [20][21][22][23][24][25][26][27]. Thus, an updated systematic review and meta-analysis is warranted to summarize the current understanding of the use of corticosteroids in patients undergoing heart surgery with CPB.…”
Section: Introductionmentioning
confidence: 99%
“…The prophylactic administration of steroid, with the aim of improving the post-operative patient outcomes in surgeries involving CPB, has shown mixed results in clinical trials Supplementary Table 2. Multiple studies have found that corticosteroid-related attenuation of the inflammation and tissue injury and oxidative stress, is associated with improvement of post-operative contractile function of the heart, lower incidence of post-operative atrial fibrillation (AF), decreased requirement for ventilator and circulatory support, and shorter length of hospital and ICU stay without increasing the risk of infections (171)(172)(173)(174)(175)(176)(177)(178)(179)(180). Still, some other studies have not detected any beneficial effects for corticosteroid administration in improving post-operative primary and secondary outcomes (173)(174)(175)(176)180).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Multiple studies have found that corticosteroid-related attenuation of the inflammation and tissue injury and oxidative stress, is associated with improvement of post-operative contractile function of the heart, lower incidence of post-operative atrial fibrillation (AF), decreased requirement for ventilator and circulatory support, and shorter length of hospital and ICU stay without increasing the risk of infections (171)(172)(173)(174)(175)(176)(177)(178)(179)(180). Still, some other studies have not detected any beneficial effects for corticosteroid administration in improving post-operative primary and secondary outcomes (173)(174)(175)(176)180). Despite the mixed findings, meta-analytical studies suggests that prophylactic corticosteroids in patients undergoing cardiac surgery involving CPB significantly decreases the length of stay in ICU and hospital and incidence of post-operation AF in both adult and pediatric patient populations, and decreased inflammation has been suggested to be one of the key element in these effects (181)(182)(183).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Various pharmacological interventions have been tried to reduce inflammatory responses during on-pump cardiac surgery. [4][5][6] Regional anesthesia with local anesthetics has been shown to inhibit the stress response to surgery and can also influence the postoperative outcome by its beneficial effects on organ function. [7][8][9] In addition to reliable analgesia, intrathecal and epidural anesthesia produce thoracic cardiac sympathectomy and may attenuate stress response in patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%